A secondary battery

CN122968232APending Publication Date: 2026-10-23ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611143025.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

传统石墨负极材料的理论比容量仅为372mAh/g,难以满足高能量密度电池的需求

Benefits of technology

[0028]本发明二次电池的负极片中第二负极活性层采用小颗粒、低石墨化度的第二石墨,提供高比表面积和丰富的活性离子传输通道,同时,较高的第二聚丙烯腈类粘接剂含量有利于活性层中形成连续导电网络,二者共同作用显著提升活性离子传输速率,满足高倍率充放电需求;第一负极活性层采用大颗粒、高压实的第一石墨形成稳定骨架,结合高模量、低含量的第一聚丙烯腈类粘接剂,有效吸收负极活性材料的体积膨胀应力,抑制电极粉化和负极集流体剥离。该二次电池采用双层梯度设计解决了传统硅基负极的快充性能与结构稳定性矛盾,从而在高倍率充放电条件下实现二次电池快充性能、能量密度和循环寿命的协同优化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968232A_ABST
    Figure CN122968232A_ABST
Patent Text Reader

Abstract

The application provides a secondary battery. The secondary battery comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector; in the thickness direction of the negative electrode current collector, the negative electrode active layer comprises a first negative electrode active layer and a second negative electrode active layer which are arranged in a stacked manner, and the first negative electrode active layer is located between the negative electrode current collector and the second negative electrode active layer; the first negative electrode active layer comprises first graphite, a first polyacrylonitrile-based binder and first solid electrolyte particles; the second negative electrode active layer comprises a silicon-based material, second graphite, a second polyacrylonitrile-based binder and second solid electrolyte particles; the secondary battery satisfies A2-A1=0.5%-2.5% and B1B2. The secondary battery provided by the application has excellent energy density and cycle stability under fast charging conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of secondary battery technology, and particularly relates to a secondary battery. Background Technology

[0002] With the rapid development of electric vehicles, smart wearable devices, and high-performance energy storage systems, secondary batteries, as core energy carriers, have seen their energy density, cycle performance, and fast-charging performance become key bottlenecks restricting technological breakthroughs. The theoretical specific capacity of traditional graphite anode materials is only 372 mAh / g, which is insufficient to meet the demands of high-energy-density batteries. Silicon-based materials, due to their extremely high theoretical specific capacity (approximately 4200 mAh / g), are considered strong candidates for next-generation anode materials. However, they exhibit significant volume effects during charge and discharge. These volume changes lead to problems such as electrode structure damage, active material shedding, and continuous growth of the solid electrolyte interphase (SEI) film on the surface of the active material, severely limiting the improvement of battery cycle life and fast-charging performance.

[0003] In practical applications, secondary batteries using silicon-based materials as negative electrode active materials cannot simultaneously meet the requirements of high energy density, fast charging performance, and long cycle stability. The batteries often exhibit problems such as increased internal resistance and rapid capacity decay.

[0004] Therefore, there is an urgent need for a rechargeable battery that can improve fast charging dynamics while maintaining high energy density and ensuring long-cycle stability. Summary of the Invention

[0005] This invention provides a secondary battery that exhibits excellent energy density and cycle stability under fast charging conditions.

[0006] The first aspect of the present invention provides a secondary battery, including a negative electrode sheet, the negative electrode sheet including a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector; in the thickness direction of the negative electrode current collector, the negative electrode active layer includes a first negative electrode active layer and a second negative electrode active layer stacked thereon, the first negative electrode active layer being located between the negative electrode current collector and the second negative electrode active layer;

[0007] The first negative electrode active layer comprises a first graphite, a first polyacrylonitrile binder, and first solid electrolyte particles; the particle size Dv50 of the first graphite is 16-25 μm, and the graphitization degree of the first graphite is 92%-96%; in the first negative electrode active layer, the mass percentage A1 of the first polyacrylonitrile binder is 0.5%-2.5%, and the mass percentage B1 of the first solid electrolyte particles is 0.5%-2.5%;

[0008] The second negative electrode active layer comprises a silicon-based material, a second graphite, a second polyacrylonitrile binder, and second solid electrolyte particles; the particle size Dv50 of the second graphite is 8-15 μm, and the degree of graphitization of the second graphite is 90%-94%; in the second negative electrode active layer, the mass percentage A2 of the second polyacrylonitrile binder is 3.0%-5.0%, and the mass percentage B2 of the second solid electrolyte particles is 3.0%-5.0%;

[0009] The secondary battery satisfies: A2-A1=0.5%-2.5%, B1 <B2。

[0010] In the secondary battery described above, the OI value of the first graphite is 1.5-2.5; the ID / IG ratio of the first graphite in the Raman spectrum is 0.05-0.2; and / or,

[0011] The second graphite has an OI value of 1.2-1.8; in Raman spectroscopy, the second graphite has an ID / IG ratio of 0.1-0.3; and / or,

[0012] The B1 is 0.05%-1%; and / or,

[0013] The B2 value is 0.5%-3%.

[0014] In the secondary battery described above, the silicon-based material comprises silicon-carbon composite particles;

[0015] Preferably, the silicon content in the silicon-carbon composite particles is 30%-70% by mass; the ID / IG value of the silicon-carbon composite particles in Raman spectroscopy is 0.7-1.5; the median particle size of the silicon-carbon composite particles is 6-13 μm; and the average sphericity of the silicon-carbon composite particles is ≥0.85.

[0016] In the secondary battery described above, the degree of polymerization of the first polyacrylonitrile binder is 500-2000, and the weight-average molecular weight is 50,000-210,000; and / or,

[0017] The degree of polymerization of the second polyacrylonitrile adhesive is 500-2000, and the weight-average molecular weight is 50,000-210,000.

[0018] In the secondary battery described above, a groove is provided on the surface of the negative electrode active layer away from the negative electrode current collector;

[0019] Preferably, the groove has a depth of 2-30 μm, a width of 20-200 μm, and a spacing of 0.5-2.0 mm between any two adjacent grooves.

[0020] In the secondary battery described above, the negative electrode is obtained by heat treatment; wherein the heat treatment temperature is 160-180°C and the heat treatment time is 110-130 min.

[0021] The secondary battery described above further includes a separator, the separator comprising a base membrane and an adhesive layer disposed on at least one side of the base membrane, the adhesive layer comprising first polymer particles arranged in a stacked manner, the first polymer particles comprising ester-containing polymer particles, preferably polyacrylate adhesives.

[0022] In the secondary battery described above, the first polymer particles include primary particles, and on the surface of the base film with an area of ​​100×100μm, the primary particles with a particle size of less than 0.4μm account for 2%-10% of the total number of primary particles.

[0023] In the secondary battery described above, the silicon-carbon composite particles include a silicon-carbon matrix and a carbon coating layer covering the surface of the silicon-carbon matrix. The silicon-carbon matrix includes a porous carbon matrix and silicon material disposed in the pores of the porous carbon matrix.

[0024] The secondary battery described above further includes a positive electrode sheet, which comprises a positive current collector and a positive active layer located on at least one side surface of the positive current collector, the positive active layer comprising a positive active material Li. x Co 1-y Me y O2; wherein Me includes at least one of the elements Al, Zr, B, Y, Sr, W, Ti, Mg, Nb, and La; 0.95≤x≤1.05, 0<y≤0.1;

[0025] Preferably, Me includes Y and La elements, and the positive electrode active material Li x Co 1-y Me y In O2, the content of Y element is 10-800ppm and the content of La element is 10-600ppm.

[0026] The secondary battery described above further includes an electrolyte, which includes nitrile additives.

[0027] Preferably, the nitrile additive includes 1,2,4-butanetrionitrile, and the mass percentage of 1,2,4-butanetrionitrile in the electrolyte is 0.5%-5%.

[0028] In this invention, the second negative electrode active layer of the secondary battery employs small-particle, low-graphitization second graphite, providing a high specific surface area and abundant active ion transport channels. Simultaneously, a higher content of second polyacrylonitrile binder facilitates the formation of a continuous conductive network within the active layer. These two factors combined significantly enhance the active ion transport rate, meeting the demands of high-rate charge and discharge. The first negative electrode active layer utilizes large-particle, high-compact first graphite to form a stable framework. Combined with a high-modulus, low-content first polyacrylonitrile binder, it effectively absorbs the volume expansion stress of the negative electrode active material, suppressing electrode pulverization and current collector delamination. This secondary battery employs a dual-layer gradient design to resolve the contradiction between fast-charging performance and structural stability in traditional silicon-based negative electrodes, thereby achieving synergistic optimization of fast-charging performance, energy density, and cycle life under high-rate charge and discharge conditions. Attached Figure Description

[0029] Figure 1 This is a SEM image of the second negative electrode active layer of the negative electrode sheet provided in Embodiment 1 of the present invention;

[0030] Figure 2 This is a cross-sectional SEM image of the negative electrode active layer of the negative electrode sheet provided in Embodiment 1 of the present invention. Detailed Implementation

[0031] To enable rechargeable batteries to maintain high energy density and ensure long-cycle stability while improving fast-charging kinetics, the inventors researched existing rechargeable batteries and discovered that the reason they cannot achieve these performance goals simultaneously lies in the fundamental contradiction between the volume expansion problem of silicon-based anodes and the requirements for fast charging. For example, while single-layer small-particle graphite and silicon-carbon structures are beneficial for fast charging, their low compaction density leads to insufficient energy density and poor cycle life; while single-layer large-particle graphite has high energy density, its fast-charging performance is insufficient.

[0032] To address this, the present invention employs a dual-layer structure design for the negative electrode active layer, allowing the active layer materials near the current collector and near the separator to perform different functions. The electrode processing performance and overall bonding strength are ensured by adjusting the binder system. Under fast charging conditions, the significant volume change of the silicon-based material is superimposed on the rapid insertion and extraction of active ions, leading to rapid accumulation of local stress. This makes the active layer and interlayer interfaces prone to cracking, peeling, and deterioration of the conduction path. If the upper and lower layers still use similar particle sizes and binder configurations, it is difficult to simultaneously meet the needs of rapid transport near the electrolyte and the needs of framework support and stress buffering near the current collector. This can easily lead to upper layer expansion and instability, increased polarization in the lower layer, and consequently, increased battery internal resistance and accelerated capacity decay. Furthermore, insufficient kinetic and mechanical compatibility between different layers can easily cause stress concentration at the interface, resulting in poor overall electrode stability and making it difficult to meet the cycle life requirements of high-energy-density silicon-containing batteries under fast charging conditions.

[0033] Based on this, the present invention proposes a secondary battery that takes into account transmission dynamics, interface stability and cycle structure stability under fast charging conditions.

[0034] The first aspect of the present invention provides a secondary battery, including a negative electrode sheet, the negative electrode sheet including a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector; in the thickness direction of the negative electrode current collector, the negative electrode active layer includes a first negative electrode active layer and a second negative electrode active layer stacked thereon, the first negative electrode active layer being located between the negative electrode current collector and the second negative electrode active layer.

[0035] The first negative electrode active layer includes a first graphite, a first polyacrylonitrile binder, and first solid electrolyte particles; the particle size Dv50 of the first graphite is 16-25 μm, and the graphitization degree of the first graphite is 92%-96%; in the first negative electrode active layer, the mass percentage content A1 of the first polyacrylonitrile binder is 0.5%-2.5%, and the mass percentage content B1 of the first solid electrolyte particles is 0.5%-2.5%.

[0036] The second negative electrode active layer comprises a silicon-based material, a second graphite, a second polyacrylonitrile binder, and second solid electrolyte particles; the particle size Dv50 of the second graphite is 8-15 μm, and the degree of graphitization of the second graphite is 90%-94%; in the second negative electrode active layer, the mass percentage content A2 of the second polyacrylonitrile binder is 3.0%-5.0%, and the mass percentage content of the second solid electrolyte particles is B2.

[0037] The secondary battery satisfies: A2-A1=0.5%-2.5%, B1 <B2。

[0038] For example, the particle size Dv50 of the first graphite is 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm, or a range of any two of these values.

[0039] For example, the graphitization degree of the first graphite is 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, or 96%, or a range of any two of these values.

[0040] For example, the mass percentage A1 of the first polyacrylonitrile adhesive is 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.1%, 2.3%, or 2.5%, or a range of any two of these values.

[0041] For example, the particle size Dv50 of the second graphite is 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, or a range of any two of these values.

[0042] Exemplarily, the graphitization degree of the second graphite is 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5% or 94%, or a range formed by any two of these values.

[0043] Exemplarily, the mass percentage content A2 of the second polyacrylonitrile-based binder is 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8% or 5.0%, or a range formed by any two of these values.

[0044] Exemplarily, A2-A1 is 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.1%, 2.3% or 2.5%, or a range formed by any two of these values.

[0045] The secondary battery provided by the present invention has excellent energy density and cycle stability under fast charging conditions. The reasons lie in that:

[0046] On the one hand, the first negative electrode active layer on the side close to the negative electrode current collector is configured to contain first graphite with a large particle size and high graphitization degree, as well as a relatively low content of polyacrylonitrile-based binder and solid electrolyte particles, and the second negative electrode active layer on the side close to the electrolyte is configured to contain a silicon-based material, second graphite with a small particle size, a relatively high content of polyacrylonitrile-based binder and a relatively high content of solid electrolyte particles, so that the base layer (the first negative electrode active layer) is oriented to high compaction for support, while the surface layer (the second negative electrode active layer) is oriented to rapid reaction; on the other hand, by combining the control of the binder difference of A2-A1=0.5%-2.5% and the content relationship of solid electrolyte particles that B1<B2, the surface layer has a stronger accommodation capacity for the volume change of the silicon-based material, and the base layer has more stable adhesion between the entire negative electrode sheet and the negative electrode current collector, thereby reducing the interlayer interface stress concentration and the risk of pulverization and shedding of the active layer during the cycle. The combined effect of the above two aspects realizes the collaborative optimization of the negative electrode active layer in terms of structural support, ion transmission, capacity exertion and anti-swelling stability, so that the secondary battery takes into account excellent energy density and cycle stability under fast charging conditions.

[0047] In the present invention, the particle size Dv50 of the first graphite refers to the particle size when the cumulative value of the volume distribution of the first graphite is 50%, and this parameter is measured by a Malvern laser particle size analyzer.

[0048] In the present invention, the particle size Dv50 of the second graphite refers to the particle size when the cumulative value of the volume distribution of the second graphite is 50%, and this parameter is measured by a Malvern laser particle size analyzer.

[0049] The method for testing the graphitization degree of the first graphite and the second graphite in this invention is as follows: X-ray diffraction (XRD) is used, and the test is conducted using an X-ray diffractometer. The sample amount used for the test is 0.5 g / cm³. 2 The Kα line of Cu was used as the incident X-ray. The working voltage of the X-ray source was 40kV and the test power was 2kW. 2θ was used as the abscissa and the unit was °. The signal intensity was used as the ordinate. The test range was 10~80°. The scanning rate was 4° / min and the data point interval was 0.02°. Based on the position of the (002) peak of the material in the range of 2θ=22.5°-26.5°, the interlayer spacing d002 of the (002) peak was calculated by Bragg formula. Then, the graphitization degree g value was calculated by Mering-Maire formula g=(0.3440-d002) / (0.3440-0.3354).

[0050] The present invention does not specifically limit the types of the first polyacrylonitrile adhesive and the second polyacrylonitrile adhesive. The first polyacrylonitrile adhesive and the second polyacrylonitrile adhesive are each independently selected from at least one of polyacrylonitrile, modified polyacrylonitrile, resin containing acrylonitrile copolymer units, and pre-oxidized polyacrylonitrile.

[0051] The present invention does not specifically limit the types of the first solid electrolyte particles and the second solid electrolyte particles. The first solid electrolyte particles and the second solid electrolyte particles are each independently selected from at least one of oxide solid electrolyte particles, sulfide solid electrolyte particles, and halide solid electrolyte particles.

[0052] In one embodiment, the first solid electrolyte particles include, but are not limited to, LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), LLZO (Li7La3Zr2O) 12 Li3PS4, Li6PS5Cl. In one embodiment, the second solid electrolyte particles include, but are not limited to, LATP (Li3PS4, Li6PS5Cl). 1.3 Al 0.3 Ti 1.7 (PO4)3), LLZO (Li7La3Zr2O) 12 ), Li3PS4, Li6PS5Cl.

[0053] This invention does not specifically limit the type of silicon-based material, which can be at least one of nano-silicon, silicon-oxygen materials, silicon-carbon composite materials, coated silicon particles, and porous silicon particles.

[0054] The present invention does not specifically limit the types of the first graphite and the second graphite. The first graphite and the second graphite are each independently selected from at least one of natural graphite, artificial graphite, spherical graphite, surface-coated graphite, or granulated graphite.

[0055] This invention does not limit the type of material of the negative electrode current collector or the type of conductive agent. For example, the material of the negative electrode current collector can be at least one of copper foil, nickel foam, copper foam, and composite current collector; the conductive agent can be at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene.

[0056] This invention does not specifically limit the preparation method of the negative electrode sheet. In one embodiment, the preparation method of the negative electrode sheet includes:

[0057] 1) A first slurry is prepared by adding first graphite, a first polyacrylonitrile binder, first solid electrolyte particles, and a conductive agent to the solvent NMP (N-methylpyrrolidone). The first slurry is coated on at least one side of the negative electrode current collector and pre-dried to form a first negative electrode active layer. The first graphite has a particle size Dv50 of 16-25 μm and a graphitization degree of 92%-96%. In the first negative electrode active layer, the mass percentage A1 of the first polyacrylonitrile binder is 0.5%-2.5%, and the mass percentage B1 of the first solid electrolyte particles is 0.1%.

[0058] 2) A second slurry is prepared by adding silicon-based material, second graphite, second polyacrylonitrile binder, second solid electrolyte particles, and conductive agent to a solvent. The second slurry is coated onto the surface of the first negative electrode active layer, and the negative electrode sheet is obtained after drying, rolling, and cutting. The particle size Dv50 of the second graphite is 8-15 μm, and the graphitization degree of the second graphite is 90%-94%. In the second negative electrode active layer, the mass percentage A2 of the second polyacrylonitrile binder is 3.0%-5.0%, and the mass percentage B2 of the second solid electrolyte particles is 3.0%-5.0%. The secondary battery satisfies: A2-A1=0.5%-2.5%, B1 <B2。

[0059] In one embodiment, the first negative electrode active layer comprises, by mass percentage, 93.5%-99% of first graphite, 0.5%-2.5% of first polyacrylonitrile binder, 0.05%-1% of first solid electrolyte particles, and 0.2%-3% of conductive agent.

[0060] In one embodiment, the second negative electrode active layer comprises, by weight percentage, 17.2%-75.6% silicon-based material, 18.9%-68.8% second graphite, 3%-5% second polyacrylonitrile binder, 0.5%-3% second solid electrolyte particles, and 2%-6% conductive agent.

[0061] This invention does not specifically limit the preparation method of the secondary battery. In one embodiment, the preparation method of the secondary battery includes:

[0062] The above-mentioned negative electrode sheet, separator and positive electrode sheet are wound to obtain a bare cell. The bare cell is placed in a battery aluminum shell / soft pack aluminum-plastic film, top sealed, side sealed, dried to remove moisture, and then an electrolyte (EC, DMC and EMC are mixed in a volume ratio of 3:4:3) is injected into the battery shell, top sealed, formed and sorted to obtain a secondary battery.

[0063] The electrolyte of the present invention further includes ethylene carbonate (EC), propylene carbonate, butene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, methyl ethyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, and γ-butyrolactone.

[0064] The electrolyte of the present invention also includes a lithium salt, which may be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0065] In one specific embodiment, the OI value of the first graphite is 1.5-2.5; and the ID / IG ratio of the first graphite in Raman spectroscopy is 0.05-0.2. Controlling the OI value and ID / IG within the above ranges results in the first graphite having a higher degree of order and a lower defect density, which is beneficial for improving electron conduction and compaction density, thereby enhancing the structural support capability of the first negative electrode active layer.

[0066] For example, the OI value of the first graphite is 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or 2.5, or a range of any two of these values.

[0067] For example, the ID / IG of the first graphite is 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.12, 0.14, 0.16, 0.18 or 0.2, or a range of any two of these values.

[0068] The OI value of the first graphite in this invention is tested using X-ray diffraction (XRD).

[0069] In one specific embodiment, the OI value of the second graphite is 1.2-1.8; and the ID / IG ratio of the second graphite in Raman spectroscopy is 0.1-0.3. By controlling the OI value and ID / IG within the above ranges, the second graphite possesses both a certain degree of order and a moderate number of defect sites, improving the insertion / extraction kinetics of active ions. Therefore, it is more suitable for placement near the electrolyte side to enhance the fast-charging response of the secondary battery.

[0070] For example, the OI value of the second graphite is 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or 1.8, or a range of any two of these values.

[0071] For example, the ID / IG of the second graphite is 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28 or 0.3, or a range of any two of these values.

[0072] The OI value of the second graphite in this invention is tested using X-ray diffraction (XRD).

[0073] In one specific embodiment, B1 is 0.05%-1%. With B1 being 0.05%-1%, the content of solid electrolyte particles in the first negative electrode active layer is relatively low, which reduces interference with compaction and skeleton continuity while ensuring basic ion channels, thereby balancing the fast charging performance and energy density of the secondary battery.

[0074] For example, B1 is 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%, or a range of any two of these values.

[0075] In one specific embodiment, B2 is 0.5%-3%. With B2 at 0.5%-3%, the content of solid electrolyte particles in the second negative electrode active layer is higher, which can increase the ion transport interface and buffer the volume change of silicon-based materials, thereby improving the fast charging performance and cycle stability of the secondary battery.

[0076] For example, B2 is 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.1%, 2.3%, 2.5%, 2.7%, 2.9%, or 3%, or a range of any two of these values.

[0077] When both the first and second graphite satisfy the above-mentioned OI value and ID / IG, and B1 and B2 simultaneously satisfy the above-mentioned ranges, the first and second negative electrode active layers achieve high support and low impedance on the side near the negative electrode current collector and fast transport and strong buffering synergy on the side near the electrolyte through gradient matching of graphite order, defect degree and solid electrolyte particle content, thereby reducing polarization, suppressing cracking and peeling and improving cycle life.

[0078] In one specific embodiment, the silicon-based material includes silicon-carbon composite particles; preferably, the silicon content in the silicon-carbon composite particles is 30%-70% by mass; in Raman spectroscopy, the ID / IG value of the silicon-carbon composite particles is 0.7-1.5; the median particle size of the silicon-carbon composite particles is 6-13 μm; and the average sphericity of the silicon-carbon composite particles is ≥0.85. The silicon-carbon composite particles can absorb the volume change of silicon during lithium insertion / extraction processes through the conductive network and buffer framework of the carbon phase, thereby reducing the risk of particle pulverization and electrode cracking. Through the synergistic optimization of the silicon content, structural defects, median particle size, and morphology parameters, the silicon-carbon composite particles can quickly respond to active ion transport and effectively release volume expansion stress under fast charging conditions, thereby improving the structural integrity, interface stability, and cycle durability of the negative electrode active layer, and ultimately improving the rate performance, capacity retention, and fast charging life of the secondary battery.

[0079] For example, the mass content of silicon in the silicon-carbon composite particles is 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%, or a range of any two of these values.

[0080] For example, the ID / IG value of the silicon-carbon composite particles is 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4 or 1.5, or a range of any two of these values.

[0081] For example, the median particle size of the silicon-carbon composite particles is 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or 13 μm, or a range of any two of these values.

[0082] For example, the average sphericity of the silicon-carbon composite particles is 0.85, 0.86, 0.87, 0.88, 0.9, 0.91, 0.92, 0.93, 0.94 or above, or a range consisting of any two of these values.

[0083] The method for testing the mass content of silicon in silicon-carbon composite particles in this invention is as follows:

[0084] Using a thermogravimetric analyzer, the sample size was 5-15 mg. The temperature was increased from room temperature to 900℃ at a rate of 10℃ / min in an air or oxygen atmosphere, and held at 900℃ for 40 min. This allowed the non-silicon components in the silicon-carbon composite particles to volatilize while the silicon was fully oxidized to silicon dioxide. The weight percentage at the end of the entire test process was the ash content. Dividing the ash content by the molar mass of silicon dioxide (60) and then multiplying by the molar mass of silicon (28) yielded the mass content of silicon in the silicon-carbon composite particles.

[0085] Alternatively, the battery can be discharged to 0% SOC, disassembled, cleaned, dried, and sampled. Then, an EDS test is performed on the cross-section of the negative electrode of the battery, and the average value of the EDS scan results of multiple silicon-carbon composite particles is taken as the mass content of silicon in the silicon-carbon composite particles.

[0086] The method for testing the median particle size of silicon-carbon composite particles in this invention is as follows:

[0087] Pre-disperse 10-50 mg of sample in a liquid medium such as water or ethanol, and then measure it after fully dispersing it by sonication and circulation.

[0088] Add clean dispersion medium to the circulation chamber and run a background test to ensure a clean background. Add sample: Slowly add the well-dispersed sample suspension dropwise until the opacity reaches the instrument's recommended range (usually between 5% and 15%). Set the speed between 300 and 800 rpm to ensure uniform particle circulation in the chamber without bubble formation. Click to measure and record data such as D10, D50, and D90. It is recommended to sample the same sample 2-3 times to observe the repeatability of the results (generally, the relative deviation of D50 should be <3%).

[0089] The method for testing the average sphericity of silicon-carbon composite particles in this invention is as follows: Using a scanning electron microscope (SEM) to observe the surface of the second negative electrode active layer, 200 silicon-carbon composite particles are randomly selected as test samples. The test samples are observed using SEM, and combined with image analysis software, the radius r1 of the equivalent circle representing the projected circumference of a single silicon-carbon composite particle and the radius r2 of the equivalent circle representing the projected area of ​​the silicon-carbon composite particle are calculated. The sphericity of a single silicon-carbon composite particle is calculated as r2 / r1. The average sphericity of the 200 silicon-carbon composite particles is then calculated. This process is repeated 5 times, and the average value is taken as the final test result. It is understood that if no 200 silicon-carbon composite particles are observed in the image, multiple images are taken, and the average sphericity of the total 200 silicon-carbon composite particles is taken as the average sphericity of the silicon-carbon composite particles.

[0090] In one specific embodiment, the degree of polymerization of the first polyacrylonitrile adhesive is 500-2000, and the weight-average molecular weight is 50,000-210,000. Controlling the degree of polymerization and weight-average molecular weight of the first polyacrylonitrile adhesive within the above range ensures coating processability while forming a continuous and dense adhesive network, which further helps maintain structural support near the negative electrode current collector.

[0091] The method for testing the degree of polymerization of the first polyacrylonitrile adhesive in this invention is as follows: the sample containing the adhesive to be tested is immersed in N-methylpyrrolidone (NMP) solvent containing 1 wt% LiBr, ultrasonically treated for 30 min (power 200W), and after centrifugation, the supernatant is taken for gel permeation chromatography (GPC) to test, and the number average molecular weight is measured to obtain the degree of polymerization.

[0092] The method for testing the weight-average molecular weight of the first polyacrylonitrile adhesive in this invention is as follows: the weight-average molecular weight of the polymer in the adhesive is tested by gel permeation chromatography (GPC).

[0093] For example, the degree of polymerization of the first polyacrylonitrile adhesive is 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900 or 2000, or a range of any two of these values.

[0094] For example, the weight-average molecular weight of the first polyacrylonitrile adhesive is 50,000, 70,000, 90,000, 110,000, 130,000, 150,000, 170,000, 180,000, 190,000, 200,000 or 210,000, or a range of any two of these values.

[0095] In one specific embodiment, the degree of polymerization of the second polyacrylonitrile adhesive is 500-2000, and the weight-average molecular weight is 50,000-210,000. Controlling the degree of polymerization and weight-average molecular weight of the second polyacrylonitrile adhesive within these ranges ensures coating processability while forming a continuous and dense adhesive network, which further helps to buffer volume changes in the silicon-based material and maintain the integrity of the transport channels.

[0096] For example, the degree of polymerization of the second polyacrylonitrile adhesive is 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900 or 2000, or a range of any two of these values.

[0097] For example, the weight-average molecular weight of the second polyacrylonitrile adhesive is 50,000, 70,000, 90,000, 110,000, 130,000, 150,000, 170,000, 180,000, 190,000, 200,000 or 210,000, or any range of two such values.

[0098] The method for testing the degree of polymerization of the second polyacrylonitrile adhesive in this invention is the same as the method for testing the degree of polymerization of the first polyacrylonitrile adhesive.

[0099] The method for testing the weight-average molecular weight of the second polyacrylonitrile adhesive in this invention is the same as the method for testing the weight-average molecular weight of the first polyacrylonitrile adhesive.

[0100] In one specific embodiment, a groove is formed on the surface of the negative electrode active layer away from the negative electrode current collector; preferably, the groove has a depth of 2-30 μm, a width of 20-200 μm, and a spacing of 0.5-2.0 mm between any two adjacent grooves. The groove on the surface of the negative electrode active layer constructs a local buffer and transport composite structure, providing additional channels for electrolyte wetting, active ion diffusion, and volume changes during charging and discharging. This weakens concentration polarization caused by surface active ion accumulation under fast charging conditions and alleviates surface cracking and peeling caused by active layer drying shrinkage or cyclic expansion. By controlling the groove parameters within the above range, a stress release space is formed while maintaining the continuous conductive network of the active material, releasing the stress from drying shrinkage and lithium intercalation expansion, and providing local support for the electrode structure, thereby improving the cycle stability and capacity retention of the secondary battery.

[0101] For example, the depth of the groove is 2μm, 5μm, 8μm, 11μm, 14μm, 17μm, 20μm, 23μm, 26μm, 29μm or 30μm, or a range of any two of these values.

[0102] For example, the width of the groove is 20μm, 40μm, 60μm, 80μm, 100μm, 120μm, 140μm, 160μm, 180μm, 190μm or 200μm, or a range of any two of these values.

[0103] For example, the spacing between any two adjacent grooves is 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm or 2μm, or a range of any two of these values.

[0104] In this invention, the groove parameters can be obtained by conventional methods in the art, such as by using a 3D profilometer or by cropping and statistically averaging multiple groove parameters from a SEM image.

[0105] In one specific embodiment, the negative electrode sheet is obtained through heat treatment; wherein the heat treatment temperature is 160-180℃ and the heat treatment time is 110-130 min. After this heat treatment process, the linear molecular chains of the binder undergo cyclization, dehydrogenation, and oxidative cross-linking reactions to construct a three-dimensional network structure. Furthermore, the adhesion in the coating becomes denser and more uniform, and the mechanical strength is significantly improved, allowing for better utilization of its mechanical strength and enhancing the interfacial stability of the negative electrode. This effectively suppresses silicon particle expansion, reduces charge transfer impedance, and contributes to improving the structural stability and electrochemical performance of the negative electrode sheet.

[0106] For example, the heat treatment temperature is 160°C, 162°C, 164°C, 166°C, 168°C, 170°C, 172°C, 174°C, 176°C, 178°C, or 180°C, or a range of any two of these values.

[0107] For example, the heat treatment time is 110 min, 112 min, 114 min, 116 min, 118 min, 120 min, 122 min, 124 min, 126 min, 128 min or 130 min, or a range of any two of these values.

[0108] To further improve the contact uniformity between the electrode and the separator, and to reduce separator wrinkles, slippage, and internal resistance fluctuations, thereby enhancing the safety, rate stability, and cycle life of the secondary battery, the separator was improved.

[0109] In one specific embodiment, the secondary battery further includes a separator, which comprises a base film and an adhesive layer disposed on at least one side of the base film. The adhesive layer includes first polymer particles arranged in a stacked manner. The first polymer particles include ester-containing polymer particles, preferably polyacrylate adhesives. The adhesive layer enhances the adhesion stability between the separator and the electrode surface. Simultaneously, the stacked first polymer particles form a multi-point stacked flexible contact structure on the base film surface, maintaining appropriate porosity to ensure electrolyte wetting and active ion passage, while also providing buffer space during assembly and cyclic expansion, reducing the risk of interface delamination. The first polymer particles, including ester-containing polymer particles, utilize the polarity and flexibility provided by the ester groups to improve compatibility and wettability with the positive and negative electrode coatings, the separator base film, and the electrolyte.

[0110] This invention does not specifically limit the type of base film, including but not limited to polyethylene film and polypropylene film.

[0111] In one specific embodiment, the first polymer particles include primary particles. On the surface of a base film with an area of ​​100×100μm, primary particles with a diameter less than 0.4μm account for 2%-10% of the total number of primary particles. Within this range, the adhesive layer can form a continuous covering structure on the base film surface, enhancing the interfacial stability between the separator and adjacent electrode layers, and maintaining suitable pore structure and ion transport efficiency, thereby improving the rate performance and cycle life of the secondary battery under fast charging conditions.

[0112] For example, primary particles with a diameter less than 0.4 μm account for 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% of the total number of primary particles, or a range of any two of these values.

[0113] In this invention, the percentage of primary particles with a diameter less than 0.4 μm in the total number of primary particles is determined by scanning electron microscopy (SEM). Specifically, on the surface or cross-section of the adhesive layer, SEM images taken at 1000x magnification are used to measure and count the particle size of all primary particles of the first polymer in the image. If the number of primary particles in a single image is insufficient, multiple images can be taken until the number of observed primary particles reaches 800. Subsequently, the number of particles with a diameter less than 0.4 μm is counted, and the ratio of this number to the total number of counted particles (800) is the percentage of particles with a diameter less than 0.4 μm in the total number of silicon-based material particles.

[0114] In one specific embodiment, the silicon-carbon composite particle includes a silicon-carbon matrix and a carbon coating layer covering the surface of the silicon-carbon matrix. The silicon-carbon matrix includes a porous carbon matrix and silicon material disposed in the pores of the porous carbon matrix. By disposing of the silicon material in the pores of the porous carbon matrix, the stress generated by the silicon material during lithium intercalation can be dispersed to the pore walls and carbon skeleton, avoiding local stress concentration. The stable interface formed by the outer carbon coating layer can reduce SEI film rupture and side reactions caused by repeated expansion and contraction. At the same time, it improves the overall conductivity of the particle. Thus, the silicon-carbon composite particle can maintain a high capacity retention rate, low impedance growth, and more stable structural integrity under fast charging and long cycling conditions.

[0115] The present invention does not specifically limit the type of porous carbon matrix, but preferably includes at least one of mesoporous carbon, hard carbon, soft carbon, and graphene framework carbon.

[0116] The present invention does not specifically limit the type of silicon material, but preferably includes at least one of nano-silicon, micro-nano silicon oxide material, and silicon particles.

[0117] The present invention does not specifically limit the method of placing silicon material in the pores of a porous carbon matrix, but preferably it is done by at least one of vapor deposition, impregnation, melt infiltration and mechanical embedding.

[0118] In one specific embodiment, the secondary battery further includes a positive electrode sheet, which comprises a positive current collector and a positive active layer located on at least one side surface of the positive current collector. The positive active layer comprises a positive active material Li. x Co 1-y Me y O2; wherein Me includes at least one of the elements Al, Zr, B, Y, Sr, W, Ti, Mg, Nb, and La; 0.95 ≤ x ≤ 1.05, 0 < y ≤ 0.1. For example, x is 0.95, 0.97, 0.99, 1.01, 1.03, or 1.05, or a range consisting of any two of these values.

[0119] For example, y is 0.01, 0.03, 0.05, 0.07, 0.09, or 0.1, or a range of any two of these values.

[0120] When Me is a mixture of the aforementioned substances, the present invention does not specifically limit the proportion of each specific substance in the mixture.

[0121] The aforementioned cathode active materials utilize one or more elements to substitute or regulate cobalt sites, thereby adjusting lattice energy, suppressing cation mixing, reducing phase transition tendency under high temperature and high voltage, and improving interfacial stability of the cathode active material surface. When appropriate doping elements enter the layered lattice, they can enhance the stability of the oxygen octahedral structure in the active material lattice, slow down lattice collapse and microcrack propagation during cycling, and thus improve the rate performance and cycle life of the secondary battery.

[0122] This invention does not impose any particular limitation on the positive electrode current collector; any conventional positive electrode current collector in the art can be used. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil, carbon-coated aluminum foil, composite current collector, etc.

[0123] In one specific embodiment, Me includes Y and La elements, and the positive electrode active material is Li. x Co 1-y Me yIn O2, the content of Y element is 10-800 ppm, and the content of La element is 10-600 ppm. The above-mentioned trace range setting allows Y and La to achieve grain growth control, interfacial side reaction suppression, and thermal stability improvement with extremely low addition amounts, while taking into account the active sites or discharge capacity of the positive electrode active material. This enables the positive electrode active material to maintain low polarization and more stable capacity output under fast charging, long cycle and high operating voltage conditions, thereby ensuring that the secondary battery has both high energy density, good rate performance and long cycle life.

[0124] For example, the positive electrode active material Li x Co 1-y Me y In O2, the Y content is 10ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm or 800ppm, or a range of any two of these values.

[0125] For example, the positive electrode active material Li x Co 1-y Me y In O2, the La content is 10ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm or 600ppm, or a range of any two of these values.

[0126] In this invention, the positive electrode active material Li x Co 1-y Me y The contents of Y and La in O2 were determined by inductively coupled plasma optical emission spectrometry (ICP-OES).

[0127] In one specific embodiment, the secondary battery further includes an electrolyte comprising nitrile additives. Because nitrile groups have strong polarity and a high film-forming tendency, they can be preferentially consumed in interfacial side reactions under fast charging and high voltage conditions, suppressing the continuous decomposition of conventional solvents, thereby reducing interfacial impedance growth and the risk of gas evolution, and thus improving the cycle life of the secondary battery.

[0128] In one specific embodiment, the nitrile additive includes 1,2,4-butanetrionitrile, and the mass percentage of 1,2,4-butanetrionitrile in the electrolyte is 0.5-5%. This range of addition allows the electrolyte to improve high-voltage stability and cycle stability while ensuring its transport capacity, further mitigating interfacial instability, increased internal resistance, and capacity decay during fast charging, thereby improving the cycle life, safety, and overall electrochemical performance of the secondary battery.

[0129] For example, the mass percentage of 1,2,4-butanetrionitrile in the electrolyte is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%, or a range of any two of these values.

[0130] This invention utilizes gas chromatography-mass spectrometry (GC-MS) to determine the mass percentage of 1,2,4-butanetrionitrile in the electrolyte.

[0131] The present invention will be further described below through specific embodiments.

[0132] Example 1

[0133] The method for preparing the negative electrode sheet in this embodiment includes the following steps:

[0134] 1) Preparation of the second slurry:

[0135] The second type of graphite is fast-charging small-particle graphite (Dv50=12μm, OI=1.2, graphitization degree 92%, ID / IG=0.10).

[0136] A mixture of silicon-carbon material (ID / IG value of 1.0, median particle size of 250 nm, and average sphericity of 0.95) (content of 80 wt%), second graphite (artificial graphite, content of 20 wt%), conductive material (60 wt% CNT carbon nanotubes and 40 wt% carbon black), second polyacrylonitrile binder (degree of polymerization of 1000, weight-average molecular weight of 150,000), and second binder PVDF (weight-average molecular weight of 800,000, degree of polymerization of 12,500) was mixed and stirred at a mass ratio of 92:3:4:1. NMP solvent was added and stirred. The pH of the slurry was adjusted to 8, the actual temperature of the mixing tank was kept ≤60℃, the viscosity was adjusted to 4500 mPa·s, and the solid content was controlled at 30% to obtain the second negative electrode slurry.

[0137] 2) Preparation of the first slurry:

[0138] The first type of graphite is a high-energy-density, large-particle graphite (D50=20μm, OI=2.0, graphitization degree 95%, ID / IG=0.05).

[0139] The first graphite (artificial graphite, 100wt%), conductive material (60wt% CNT carbon nanotubes and 40wt% carbon black), the first polyacrylonitrile binder (degree of polymerization 1000, weight average molecular weight 150,000), and the first binder PVDF (weight average molecular weight 800,000, degree of polymerization 12,500) were mixed and stirred in a mass ratio of 95.5:2:2:0.5. The solvent NMP was added and stirred. The pH of the slurry was adjusted to 8, the actual temperature of the mixing tank was kept ≤60℃, the viscosity was adjusted to 5800 mPa·s, and the solid content was controlled at 38% to obtain the first slurry.

[0140] 3) Preparation of the negative electrode:

[0141] A first slurry is first coated onto the copper foil current collector, with an areal density of 2.84 mg / cm³. 2 The carbon-coated copper foil with a thickness of 6 μm was uniformly coated on both sides and pre-dried at 80°C for 1 minute to obtain the first negative electrode active layer; then immediately coated with a carbon-coated copper foil with an areal density of 2.96 mg / cm³. 2 The second slurry was coated onto the surface of the first negative electrode active layer; it was then thoroughly dried at 100°C; subsequently, it was rolled to a density of 1.70 g / cm³. 3 Compacted density; Laser wire drawing is performed to create grooves: depth 15μm, width 80μm, and the distance between any two adjacent grooves is 1.5mm. Then, after heat treatment at 170℃ for 2 hours under nitrogen protection, the tabs are welded to obtain the negative electrode sheet.

[0142] The method for preparing the positive electrode sheet in this embodiment includes the following steps:

[0143] (1) The positive electrode active material lithium cobalt oxide, conductive agent (30wt% CNT carbon nanotubes and 70wt% carbon black) and binder (polyvinylidene fluoride) are made into a positive electrode slurry in a mass ratio of 98:1:1. The slurry is coated on a 9μm aluminum foil and dried, rolled, slit and cut into pieces. Then the tabs are welded to make a positive electrode sheet.

[0144] (2) Preparation of the diaphragm: Boehmite, methacrylic acid, and sodium polymethyl cellulose were added to deionized water and stirred thoroughly to obtain a coating slurry with a solid content of 15%. Based on the 100% solid mass of the slurry, the weight ratio of boehmite, methacrylic acid, and sodium polymethyl cellulose was 92:4:4. The coating slurry was coated onto one side of the polyethylene substrate layer using a gravure roller and dried in a multi-section oven at 60°C to form a coating. The first polymethyl methacrylate (PMMA, with an average particle size of 0.6 μm) particles were dispersed in deionized water. In the agent, after thorough stirring, a first adhesive layer slurry with a solid content of 10% is obtained. The coating slurry is applied to the surface of the other side of the substrate layer by a gravure roller. After drying in a multi-section oven at 60°C, the first adhesive layer is formed. The first PMMA particles (average particle size of 0.6μm) and the second particles (PVDF) are dispersed in a deionized water solvent. After thorough stirring, a second adhesive layer slurry with a solid content of 10% is obtained. The second adhesive layer slurry is applied to the surface of the coating by a gravure roller. After drying in a multi-section oven at 60°C, the second adhesive layer is formed, thus obtaining the diaphragm.

[0145] (3) The bare cell is obtained by winding the negative electrode, separator, and positive electrode in sequence. The bare cell is placed in a soft-pack aluminum-plastic film, top-sealed, side-sealed, and dried to remove moisture. Electrolyte (EC, DMC, and EMC are mixed in a volume ratio of 3:4:3) is injected, top-sealed, formed, and sorted to obtain a secondary battery. The electrolyte includes a mixed solvent of EC, DMC, and EMC in a volume ratio of 3:4:3, and based on the total mass of the electrolyte, 15wt% LiPF6, 10wt% LITFSI, 10wt% FEC, and 2wt% 1,2,4-butanetrionitrile are added.

[0146] Example 2 - Comparative Example 14 is basically the same as Example 1, except that the differences are shown in Tables 1A-3B.

[0147] Experimental Example 1

[0148] 1. The particle size Dv50, graphitization degree, OI value, ID / IG, A1, B1, A2, and B2 of the first and second graphite in the negative electrode sheets of the examples and comparative examples were tested; the ID / IG value, median particle size, average sphericity, and silicon content of the silicon-carbon composite particles in the negative electrode sheets of the examples and comparative examples were tested; the first polyacrylonitrile binder and the second polyacrylonitrile binder in the negative electrode sheets of the examples and comparative examples were tested. The degree of polymerization and weight-average molecular weight of the adhesive were tested; the depth, width, and spacing between any two adjacent grooves of the grooves were tested; the proportion of primary polymer particles with a particle size of less than 0.4 μm in the diaphragms of the examples and comparative examples was tested; the type, Y content, and La content of the positive electrode active material of the examples and comparative examples were tested; and the mass percentage of 1,2,4-butanetrionitrile in the electrolyte of the examples and comparative examples was tested. The results are shown in Tables 1A-3B.

[0149] 2. Testing Methods

[0150] 1) Test methods for particle size Dv50, degree of graphitization, and OI value of first and second graphite.

[0151] The particle size Dv50 was measured using a Malvern laser particle size analyzer.

[0152] Graphitization degree: Measured using X-ray diffraction (XRD) with an X-ray diffractometer. The sample amount used for testing was 0.5 g / cm³. 2 The Kα line of Cu was used as the incident X-ray. The working voltage of the X-ray source was 40kV and the test power was 2kW. 2θ was used as the abscissa and the unit was °. The signal intensity was used as the ordinate. The test range was 10~80°. The scanning rate was 4° / min and the data point interval was 0.02°. Based on the position of the (002) peak of the material in the range of 2θ=22.5°-26.5°, the interlayer spacing d002 of the (002) peak was calculated by Bragg formula. Then, the graphitization degree g value was calculated by Mering-Maire formula g=(0.3440-d002) / (0.3440-0.3354).

[0153] The OI value is tested using X-ray diffraction (XRD).

[0154] 2) Test methods for silicon content, median particle size, and average sphericity in silicon-carbon composite particles.

[0155] Mass content of silicon in silicon-carbon composite particles: A thermogravimetric analyzer was used, with a sample size of 5-15 mg. The temperature was increased from room temperature to 900°C at a rate of 10°C / min in an air or oxygen atmosphere, and held at 900°C for 40 min. This allowed the non-silicon components in the silicon-carbon composite particles to volatilize while the silicon was fully oxidized to silicon dioxide. The weight percentage at the end of the entire test process was the ash content. The ash content was then divided by the molar mass of silicon dioxide (60) and multiplied by the molar mass of silicon (28) to obtain the mass content of silicon in the silicon-carbon composite particles.

[0156] Alternatively, the battery can be discharged to 0% SOC, disassembled, cleaned, dried, and sampled. Then, an EDS test is performed on the cross-section of the negative electrode of the battery, and the average value of the EDS scan results of multiple silicon-carbon composite particles is taken as the mass content of silicon in the silicon-carbon composite particles.

[0157] Median particle size: 10-50 mg of sample is pre-dispersed in a liquid medium such as water or ethanol, and then fully dispersed by ultrasound and circulation before measurement.

[0158] Add clean dispersion medium to the circulation chamber and run a background test to ensure a clean background. Add sample: Slowly add the well-dispersed sample suspension dropwise until the opacity reaches the instrument's recommended range (usually between 5% and 15%). Set the speed between 300 and 800 rpm to ensure uniform particle circulation in the chamber without bubble formation. Click to measure and record data such as D10, D50, and D90. It is recommended to sample the same sample 2-3 times to observe the repeatability of the results (generally, the relative deviation of D50 should be <3%).

[0159] Average sphericity: Using a scanning electron microscope (SEM) to observe the surface of the second negative electrode active layer, 200 silicon-carbon composite particles were randomly selected as test samples. The samples were observed using SEM, and combined with image analysis software, the radius r1 of the equivalent circle representing the projected circumference of a single silicon-carbon composite particle and the radius r2 of the equivalent circle representing the projected area of ​​the particle were calculated. The sphericity of a single silicon-carbon composite particle was calculated as r2 / r1. The average sphericity of the 200 silicon-carbon composite particles was then calculated. This process was repeated 5 times, and the average value was taken as the final test result. It is understood that if no 200 silicon-carbon composite particles were observed in the image, multiple images were taken, and the average sphericity of the total 200 silicon-carbon composite particles was taken as the average sphericity of the silicon-carbon composite particles.

[0160] 3) Test methods for the degree of polymerization and weight-average molecular weight of the first and second polyacrylonitrile adhesives.

[0161] Degree of polymerization: The sample containing the binder to be tested was immersed in N-methylpyrrolidone (NMP) solvent containing 1 wt% LiBr, sonicated for 30 min (power 200W), and the supernatant was centrifuged and then subjected to gel permeation chromatography (GPC) to determine the number average molecular weight and thus the degree of polymerization.

[0162] Weight-average molecular weight: The weight-average molecular weight of the polymer in the adhesive was determined by gel permeation chromatography (GPC).

[0163] 4) Test method for determining the percentage of primary particles with a diameter less than 0.4 μm in the total number of primary particles.

[0164] On the surface or cross-section of the adhesive layer, the particle size of all primary particles of the first polymer in the SEM image taken at 1000x magnification using a scanning electron microscope is measured and counted. If the number of primary particles in a single image is insufficient, multiple images can be taken until the number of observed primary particles reaches 800. Subsequently, the number of particles with a diameter less than 0.4µm is counted, and the ratio of the number of particles with a diameter less than 0.4µm to the total number of counted particles (800) is the percentage of the number of particles with a diameter less than 0.4µm in the total number of silicon-based material particles.

[0165] 5) Positive electrode active material Li x Co 1-y Me y Methods for testing the content of Y and La elements in O2

[0166] The determination was performed using inductively coupled plasma optical emission spectrometry (ICP-OES).

[0167] 6) Test method for the mass percentage of 1,2,4-butanetrionitrile in the electrolyte

[0168] The test was performed using gas chromatography-mass spectrometry (GC-MS).

[0169] Table 1A

[0170]

[0171] Table 1B

[0172]

[0173] Table 2A

[0174]

[0175] Table 2B

[0176]

[0177] Table 3A

[0178]

[0179] Table 3B

[0180]

[0181] Experimental Example 2

[0182] 1. The second negative electrode active layer of the negative electrode sheet prepared in Example 1 was subjected to SEM testing and cross-sectional SEM testing (the results are shown in [see original text]). Figure 1 , Figure 2 Peeling force, rebound after 48 hours of rolling, and peeling force of negative electrode at 0% SOC were tested. The electrochemical impedance, rate performance, and cycle performance of the secondary batteries of the examples and comparative examples were also tested. The results are shown in Tables 4A and 4B.

[0183] Depend on Figure 1 It is known that the second negative electrode active layer includes silicon-based material (spherical grayish-white substance) and graphite (blocky black substance).

[0184] Depend on Figure 2 It can be seen that the negative electrode active layer of the negative electrode sheet includes a first negative electrode active layer and a second negative electrode active layer stacked together.

[0185] 2. Testing Methods

[0186] 1) Test method for rebound after 48 hours of rolling

[0187] (1) Sampling: On the rolled electrode roll, avoid the unstable parts at the beginning and end, and cut at least 3-5 square samples of the same size (3 pieces in this test example) with uniform cutting mold. (Electrode length in this test example: 80mm×1.5m)

[0188] (2) Testing: Initial thickness measurement (H0): The first thickness measurement is performed immediately after the electrode rolling is completed. The average value is calculated as the initial thickness H0 of the sample.

[0189] Place the tray in a constant temperature and humidity environment (25℃, relative humidity <1%) and let it stand for 48 hours. Ensure that the sample is not subjected to any external pressure or interference during this period.

[0190] Final thickness measurement (H) 48 After standing for 48 hours, immediately remove the samples. Using the same micrometer, measure the thickness of each sample again at the exact same location as when measuring H0. Calculate the average value as the final thickness H of the sample. 48 .

[0191] (3) Data processing and analysis: For each sample, calculate its thickness rebound value and rebound rate.

[0192] Thickness rebound value (μm) = H 48 - H0;

[0193] Thickness rebound rate (%) = [(H 48 - H0) / H0]×100%.

[0194] 2) Test method for peel strength of 0% SOC negative electrode sheet

[0195] (1) Preparation of negative electrode sample for testing peel strength:

[0196] a. Prepare a battery that has been discharged to 2.8V (0% SOC), disassemble it and take a sample of the negative electrode. Prepare a negative electrode with a length of 78mm and a width of 24mm. The number of samples is 3 per batch.

[0197] b. Apply pressure-sensitive adhesive to the steel plate, then apply double-sided tape (length same as the steel plate, width > 24mm), attach the electrode sheet to the double-sided tape, and roll it three times to remove air bubbles and wrinkles.

[0198] c. Use a tool to separate the paste and copper foil, peel off the electrode length of 5mm in a 180° direction to ensure that the paste is continuous and does not break when measuring the peel force.

[0199] (2) Peel force test:

[0200] The steel plate is fixed to one clamp of the electric tensile testing machine, while the other clamp holds the free end of the electrode. The electrode is held at a 180° angle to the steel plate, and the paste and copper foil are then pulled apart at the test rate specified in the standard. The peel force is measured by the force required to continuously peel the paste and copper foil from the steel plate, and converted to peel strength (unit: kgf). Note that the peel line is perpendicular to the direction of the applied force.

[0201] (3) Data processing:

[0202] Record the maximum and average values, analyze the peel strength curve, remove outliers, calculate the peel force according to the formula, and take the average value of the test results. The formula for calculating the peel force is as follows:

[0203] σ 180° = (F*g) / B;

[0204] Where, σ 180° denoted as peel strength (KN / m); F as peel force (kgf); g as gravitational acceleration (m / s²); and B as sample width (mm).

[0205] 3) Electrochemical impedance spectroscopy test methods

[0206] When conducting electrochemical impedance spectroscopy (EIS) testing of lithium-ion batteries at 50% SOC in an environment of 25℃±5℃, the battery was first discharged at 0.2C to the lower limit voltage and allowed to stand for 10 minutes. Then, it was charged at a constant current of 0.7C to 3.95V, followed by constant voltage charging until the current dropped to 0.05C, with a constant voltage time of 60 minutes. It was then allowed to stand for another 10 minutes to adjust and stabilize the SOC. The AC impedance test parameters were set as follows: the highest frequency was 50kHz-5kHz (the starting frequency was the same as the highest frequency), the lowest frequency was approximately 100mHz, a scanning method from high frequency to low frequency was used, the test mode was POTENTIOSTAT, and the amplitude was 5mV. The raw data needs to be preprocessed, including integrity checks, outlier removal, and smoothing and noise reduction if necessary. After confirming the frequency range (usually 10mHz-100kHz) and the number of points, a Nyquist plot of the real part Z' and imaginary part -Z" of the impedance is drawn. At 50% SOC, this plot typically exhibits a semicircle in the high-frequency region and a diagonal line in the low-frequency region. Subsequently, a Randle or improved Randle model is selected as the equivalent circuit, and the goodness of fit (χ²) is obtained through nonlinear least squares fitting. 2 (value), and extract key parameters:

[0207] In the high-frequency region, the imaginary part Z'' of the impedance is usually close to 0. The horizontal intercept of the Nyquist plot represents the solution resistance (Rs). The impedance is mainly determined by the conductivity of the electrolyte solution, and the SEI film resistance (Rs) is also important. SEI The diameter of the first (or overlapping with the second) semicircle appearing in the high-frequency region. In the mid-frequency region, the Nyquist plot typically presents as a semicircular arc. This semicircle reflects the interaction between charge transfer impedance (Rct) and double-layer capacitance (Cdl), and its radius represents the magnitude of the charge transfer impedance.

[0208] Calculation formula: R 总 =R s +R SEI +R ct .

[0209] 4) Test methods for rate performance

[0210] The battery under test was charged and discharged at 25°C using a battery charge and discharge tester. The charge and discharge regime was as follows: constant current charging at 0.5C to the cutoff voltage (e.g., 4.5V), then constant voltage charging until the current decreased to 0.05C. After resting for 10 minutes, constant current discharging at 0.2C to the cutoff voltage (3.0V) was performed, and the discharge capacity Q was recorded. 0.2c (Initial standard capacity); After standing for 10 minutes, fully charge the battery according to the standard charging method described above, and discharge it at a constant current rate of 2C until the cutoff voltage. Record the discharge capacity Q at each rate. 2c The discharge rate capacity retention rate can be calculated using the following formula:

[0211] 2C rate discharge rate capacity retention rate = Q 2c / Q 0.2c ×100%.

[0212] 5) Cyclic performance testing methods

[0213] The capacity retention rate / thickness change rate of the secondary battery under test was tested. The specific test method was as follows: Before the test, the battery was discharged at 0.5C to 3V at 25℃ and allowed to stand for 10 minutes; then it was charged at a constant current of 0.5C to 3.95V, charged at a constant voltage of 0.05C, and allowed to stand for 10 minutes. The full-charge thickness of the battery was measured and taken as the initial thickness D0. At 25℃, the battery was charged at a constant current of 2.0C to 4.25V, charged at a constant voltage of 1.5C, then charged at a constant current of 1.5C to 4.55V, charged at a constant voltage of 0.05C, and allowed to stand for 10 minutes. Then it was discharged at 1.5C to 3.5V, then discharged at 0.7C to 3.0V and allowed to stand for 10 minutes. This charge-discharge cycle was repeated. The discharge capacity Q1 at the first cycle and the discharge capacity Q at the 500th cycle were measured. 500 Simultaneously, a full-charge thickness test is performed every 100 cycles, and the full-charge thickness D is recorded. n After the cycle test is completed, fully charge the battery as described above, let it stand at room temperature for 3 hours, and then measure the full-charge thickness D1.

[0214] Capacity retention rate Q = Q 500 / Q1*100%

[0215] Thickness change rate (%) = (D1-D0) / D0*100%.

[0216] Table 4A

[0217]

[0218] Table 4B

[0219]

[0220] As shown in Tables 4A and 4B, compared with the comparative example, the secondary battery of the present invention has excellent energy density and cycle stability under fast charging conditions.

[0221] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.

Claims

1. A secondary battery, characterized in that, The device includes a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector; in the thickness direction of the negative electrode current collector, the negative electrode active layer includes a first negative electrode active layer and a second negative electrode active layer stacked together, wherein the first negative electrode active layer is located between the negative electrode current collector and the second negative electrode active layer; The first negative electrode active layer comprises a first graphite, a first polyacrylonitrile binder, and first solid electrolyte particles; the particle size Dv50 of the first graphite is 16-25 μm, and the graphitization degree of the first graphite is 92%-96%; in the first negative electrode active layer, the mass percentage A1 of the first polyacrylonitrile binder is 0.5%-2.5%, and the mass percentage B1 of the first solid electrolyte particles is 0.5%-2.5%; The second negative electrode active layer comprises a silicon-based material, a second graphite, a second polyacrylonitrile binder, and second solid electrolyte particles; the particle size Dv50 of the second graphite is 8-15 μm, and the degree of graphitization of the second graphite is 90%-94%; in the second negative electrode active layer, the mass percentage A2 of the second polyacrylonitrile binder is 3.0%-5.0%, and the mass percentage B2 of the second solid electrolyte particles is 3.0%-5.0%; The secondary battery satisfies: A2-A1=0.5%-2.5%, B1 <B2。 2. The secondary battery according to claim 1, characterized in that, The first graphite has an OI value of 1.5-2.5; in Raman spectroscopy, the first graphite has an ID / IG ratio of 0.05-0.2; and / or, The second graphite has an OI value of 1.2-1.8; in Raman spectroscopy, the second graphite has an ID / IG ratio of 0.1-0.3; and / or, The B1 is 0.05%-1%; and / or, The B2 value is 0.5%-3%.

3. The secondary battery according to claim 1 or 2, characterized in that, The silicon-based material includes silicon-carbon composite particles; Preferably, the silicon content in the silicon-carbon composite particles is 30%-70% by mass; the ID / IG value of the silicon-carbon composite particles in Raman spectroscopy is 0.7-1.5; the median particle size of the silicon-carbon composite particles is 6-13 μm; and the average sphericity of the silicon-carbon composite particles is ≥0.

85.

4. The secondary battery according to any one of claims 1-3, characterized in that, The first polyacrylonitrile adhesive has a degree of polymerization of 500-2000 and a weight-average molecular weight of 50,000-210,000; and / or, The degree of polymerization of the second polyacrylonitrile adhesive is 500-2000, and the weight-average molecular weight is 50,000-210,000.

5. The secondary battery according to any one of claims 1-4, characterized in that, The surface of the negative electrode active layer away from the negative electrode current collector is provided with a groove; Preferably, the groove has a depth of 2-30 μm, a width of 20-200 μm, and a spacing of 0.5-2.0 mm between any two adjacent grooves.

6. The secondary battery according to any one of claims 1-5, characterized in that, The negative electrode sheet is obtained by heat treatment; wherein the heat treatment temperature is 160-180℃ and the heat treatment time is 110-130min.

7. The secondary battery according to claim 6, characterized in that, The secondary battery further includes a separator, the separator comprising a base membrane and an adhesive layer disposed on at least one side of the base membrane, the adhesive layer comprising first polymer particles arranged in a stacked manner, the first polymer particles comprising ester-containing polymer particles, preferably polyacrylate adhesives; and / or, The first polymer particles include primary particles, and on the surface of the base film with an area of ​​100×100μm, the primary particles with a particle size of less than 0.4μm account for 2%-10% of the total number of primary particles.

8. The secondary battery according to claim 3, characterized in that, The silicon-carbon composite particles include a silicon-carbon matrix and a carbon coating layer covering the surface of the silicon-carbon matrix. The silicon-carbon matrix includes a porous carbon matrix and silicon material disposed in the pores of the porous carbon matrix.

9. The secondary battery according to any one of claims 1-8, characterized in that, The secondary battery further includes a positive electrode sheet, which comprises a positive current collector and a positive active layer located on at least one side surface of the positive current collector, the positive active layer comprising a positive active material Li. x Co 1-y Me y O2; wherein Me includes at least one of the elements Al, Zr, B, Y, Sr, W, Ti, Mg, Nb, and La; 0.95≤x≤1.05, 0<y≤0.1; Preferably, Me includes Y and La elements, and the positive electrode active material Li x Co 1-y Me y In O2, the content of Y element is 10-800ppm and the content of La element is 10-600ppm.

10. The secondary battery according to any one of claims 1-9, characterized in that, The secondary battery also includes an electrolyte, which includes nitrile additives; Preferably, the nitrile additive includes 1,2,4-butanetrionitrile, and the mass percentage of 1,2,4-butanetrionitrile in the electrolyte is 0.5%-5%.